The impact of 6-week flywheel eccentric training on sprint speed and change-of-direction of female basketball players - Wuwen Peng; Wenhao Qu; Ruixiang Yan; Jiamin Xu; Hong Lin; Jian Sun; Duanying Li (PLoS ONE, 2025)
Given the demands of basketball for rapid sprinting and directional changes, and the growing interest in flywheel eccentric training (FET) to enhance these abilities, this study examines a six-week FET regimen compared to barbell squat training (BST)—the control condition—on sprint and change-of-direction performance in female collegiate basketball players.Nineteen female collegiate basketball players were randomized to flywheel eccentric training (n = 9) or barbell squat training (n = 10) groups. Both groups trained twice weekly over six weeks, following a standardized warm-up protocol. The FET group performed 4× (2 + 8) maximal concentric–eccentric repetitions on a flywheel device (inertia = 0.075 kg·m²), and the BST group completed 4 × 8 back-squat repetitions at 80% of their pre-test one-repetition maximum (1RM); all sets were separated by 3-minute rest intervals. A 2 × 2 factorial analysis of variance (ANOVA) was conducted to assess pre– to post-intervention changes in sprint speed (20-m sprint) and change-of-direction ability (505 agility test and lane agility test).The results of the analysis of variance indicated that in the FET group, the main effect of time and the interaction effect were significant for the 20m sprint and 505 agility tests (p < 0.05), while the group main effect was not significant (p > 0.05). However, no significant effects were observed for the lane agility test (p > 0.05). In the BST group, there were no significant effects regarding the main effect of time, the group main effect, or the interaction effect in any of the tests (p > 0.05). In collegiate female basketball players, six weeks of moderate-inertia (0.075 kg·m²) flywheel eccentric training elicited superior improvements in linear sprint speed and rapid direction changes ability compared to an equivalent barbell squat regimen.